Integration of evidence into Theory of Change frameworks in the healthcare sector: A rapid systematic review. - Davi Mamblona Marques Romão; Cecilia Setti; Leo Heikiti Maeda Arruda; Roberta Crevelário de Melo; Bruna Carolina de Araujo; Audrey R Tan; Peter Nichols DeMaio; Tanja Kuchenmüller (PLoS ONE)
Background Theory of Change (ToC) has become an established approach to design and evaluate interventions. While ToC should-in line with the growing international focus on evidence-informed health decision-making-consider explicit approaches to incorporate evidence, there is limited guidance on how this should be done. This rapid review aims to identify and synthesize the available literature on how to systematically use research evidence when developing or adapting ToCs in the health sector. Methods A rapid review methodology using a systematic approach, was designed. Eight electronic databases were consulted to search for peer-reviewed and gray publications detailing tools, methods, and recommendations promoting the systematic integration of research evidence in ToCs. The included studies were compared, and the findings summarized qualitatively into themes to identify key principles, stages, and procedures, guiding the systematic integration of research evidence when developing or revising a ToC. Results This review included 18 studies. The main sources from which evidence was retrieved in the ToC development process were institutional data, literature searches, and stakeholder consultation. There was a variety of ways of finding and using evidence in ToC. Firstly, the review provided an overview of existing definitions of ToC, methods applied in ToC development and the related ToC stages. Secondly, a typology of 7 stages relevant for evidence integration into ToCs was developed, outlining the types of evidence and research methods the included studies applied for each of the proposed stages. Conclusion This rapid review adds to the existing literature in two ways. First, it provides an up-to-date and comprehensive review of the existing methods for incorporating evidence into ToC development in the health sector. Second, it offers a new typology guiding any future endeavors of incorporating evidence into ToCs.